Causes of burnout syndrome and coping strategies among high dependency unit nurses of an institution in the greater Accra region of Ghana - Yaa Adomaah Boateng; Sylvia Ama Osei; Irene Korkoi Aboh; Andrew Adyei Druye (Nursing Open, 2021)
Abstract Aim The aim of this study was to determine the causes of burnout syndrome and identify strategies to cope with them among nurses at high dependency unit if a regional Hospital in Ghana. Design A descriptive convenient and purposive cross‐sectional study design was used for this study. Methods The study involved 40 nurses in the high dependency unit of the Hospital. A Maslach Burnout Inventory (MBI) was adopted to measure burnout experienced by these nurses concentrating on feelings of being emotionally exhausted and lack of energy, depersonalization, feelings of impersonal response towards patients and personal achievement. Results 62.5% of the respondents were in the high emotional exhaustion, 55% scored high in the depersonalization section and 52.5% scored high in the personal achievement (competence) on the Maslach Burnout Inventory (MBI).